ANALISIS KONSUMSI BAHAN BAKAR MOTOR BENSIN YANG TERPASANG PADA SEPEDA MOTOR SUZUKI SMASH 110CC YANG DIGUNAKAN PADA JALAN MENANJAK - Rocky Fernando Laki; Hardi Gunawan; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
This research aims to determine the fuel consumption of gasoline engine mounted on a 110cc Suzuki Smash. The data taken on the motorcycle in different gear ratios and speed for a travel distance of 1.4 km. Analysis was conducted on gear ratios-1, 2 and 3 at speeds of 10, 15, 20, 25,30,35 and 40 km / h. Observations and calculations for the a set of speed indicate that fuel consumption at gear ratio-1 is 539,9, 664,3, 770,1, 927,0, dan 989,8 g / h respectively. At gear ratio-2 is 506,8, 630,7, 730,4, 832,2 dan 982,0 g / h respectively. At gear ratio-3 is 421,7, 502,2, 558,1, 529,5 dan 721,0 g / h respectively. It is concluded that the higher the speed of the motor, the betterr the rate of consumption of fuel. From the observation it was found that the test was performed at the engine rotation range of 3210 to 6030 rpm. Results demonstrate that at the speed of 10 km / h to 40 km / h it is more efficient operate with gear ratio-2. Keywords: Fuel Consumption, Gasoline Motor, Suzuki Smash 110cc.